Representation of Personal Identity in the Contemporary Iranian Painters’ Works (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study concerns a philosophical and social approach and investigates personal identity and its aspects as a cultural topic. Nature is the essence of identity; nature returns to the heart but identity is obtained by spiritual progress. So there is no sign, we cannot speak of the nature and identity of art. All the works have an identity. It does not matter what is identity. Every work has an identity. Self-scrutiny is one of human concerns and existentialism is one of the most important topics in wisdom. From Nietzsche's perspective, personal identity is not a basic and cooperated topic, but has a cultural structure formed based on the social situation and has no stability and nature. This principle is presented beyond Good of Nietzsche in the works by Yourcenar with a permanent doubt of existence value of the subject of “I”. Nietzsche breaks down philosophy in the foreword to present a new concept for the subject of “I”. According to Nietzsche, the existence of the subject of “I” is derived from Descartes' Theory “Cogito, ergo sum"  I Think, Therefore, I am”. Nietzsche defines this belief as a grammar game without any base “beyond the Good and evil of Nietzsche, this principle is explained in the logic book that a thought comes when "it" wants to and not when "I" wish.